Windows Azure programming patterns for start-ups - Becker, Riccardo (Packt Pub., 2012)
This book follows a step-by-step approach with clear transparent instructions, screenshots and code samples. This book is intended for Microsoft .NET developers who want to leverage the power of cloud and build a brand new service from scratch; it assumes a basic understanding of the .NET framework and C♯.